Cambridge Street between Bowdoin and Scollay Square, ca. 1955 - Neiley, Robert (Tufts Archival Research Center, 2005)
View east of Cambridge Street between Bowdoin Square to the west and Scollay Square to the east. The facades of the buildings lining the street are adorned with signage and face south towards Cambridge Street. Automobiles and trucks move down Cambridge Street or are parked next to curbs. Pedestrians walk on sidewalks and across the street. The northeast side of Scollay Square is visible at the far east corner of Cambridge Street, seen at the center-left side of the photograph. The Custom House tower is visible in the background of the photograph. 7 5/8 x 9 9/16, 8 x 9 15/16 overall Photographs